Qualidade da carne e desempenho de cordeiros suplementados com óleos essenciais - Camargo, Emmanuel Veiga de (2013)
With increasing concerns for human health with the use of antibiotics, chemicals and unwanted fats intake, awakens the need for new ways to maintain the efficiency of modern livestock. The objective of this study was to evaluate animal performance, qualitative and quantitative characteristics of the carcass and instrumental and sensory quality of meat from lambs supplemented with a mixture of essential oils fatty acid profile. For this, we used 40 male not castrated, the Texel breed, weaned at approximately 60 days and housed in individual stalls, fully covered, randomly divided into five groups according to the levels of supplementation with essential oils : 0, 50mg, 100mg, 150mg and 200mg daily. The experimental diet was similar for all treatments, with daily adjustments, is aiming to keep leftovers in 10 % of the offered volume. Supplementation of capsules containing essential oils was orally administered twice a day, coinciding with the feeding periods. Proceeded to determine the biochemical energy and protein during the first thirty days experimental profile. Lambs to reach 60 % of the live weight of mature, ie, 32Kg for the animals of the Texel breed were slaughtered, with certain quantitative and qualitative characteristics of the carcass and meat. We adopted the completely randomized design and the data for each variable subjected to regression analysis. No significant influence (p <0.05) levels of essential oils was observed for the performance variables. During the characterization of biochemical profile, no influence levels of essential oils has been recorded, in addition, liver function enzymes, AST and GGT and remained stable within the limits prescribed for the species. It was also possible to identify significant influences in the qualitative and quantitative characteristics of carcasses, however, the average value for cold carcass yield was 49.11 %. Similarly, according to the regression analysis, the quantitative and qualitative characteristics of the meat have not been influenced the levels of essential oils. They were unable to determine increases in the instrumental evaluation of color or shear force. In the sensory analysis by, though not significant trained panel of meat originating from animals treated with essential oils, the lowest scores were given to the characteristic aroma of lamb meat, liver flavor and spice flavor. During evaluation of the identified fatty acids, the highest percentages were among saturated, of palmitic (C16:0) with 24.60 % and stearic (C18:0) with 19.34%, and oleic (C19:1n9) with 37.80% and linoleic (C18:2n6) with 5.84% for the unsaturated fatty acids . These fatty acids together accounted for 87.58% of the total quantified. The data observed in this study show that the participation of C14:0 in the total formation of AGS was limited in only 2.68%. Upon the advice on eating a healthy diet, the meat of lambs supplemented with essences oils can be characterized as having desirable profile.